Penerapan Metode Eksperimen Untuk Meningkatkan Hasil Belajar Energi dan Perubahannya - Nugraha, Sulaiman Wahyu; Wibowo, Agus Mukti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Energy and its changes are one of the materials taught in primary education. Learning about energy and its changes is very much related to everyday life so it is very important to master. The learning outcomes of energy and change are still quite low. The low-energy learning outcomes and changes are caused by the use of methods that do not follow the characteristics of the research material. Essay tests are used to determine understanding or learning outcomes based on the material students learn after doing activities. This study was conducted to determine the implementation of experimental methods on energy and change learning. Action Research was conducted on 21 grade IV students as a research sample. The action is carried out three times to obtain maximum results. Action results using the experimental method showed that there was a gradual increase in learning outcomes from the first, second, and third cycles